Validation and reliability of current guidelines for the treatment of essential thrombocythemia under real-world clinical settings in Japan. Issue 1 (31st December 2022) - Baba, Terumi; Hashimoto, Yoshinori; Yasuda, Hajime; Araki, Marito; Edahiro, Yoko; Morishita, Soji; Ochiai, Tomonori; Shirane, Shuichi; Ando, Jun; Komatsu, Norio
ABSTRACT: Objective: Current guidelines for essential thrombocythemia (ET) patients recommend different treatment approaches based on thrombosis risk stratification models. However, these recommendations may not be applicable to some patients under real clinical settings. Therefore, we carried out a retrospective real-world validation study. Methods: Thrombosis-free survival (TFS) was compared between treatment naïve ET patients receiving different treatment approaches. ET patients were stratified by three representative risk models, the conventional, the International Prognostic Score for thrombosis in ET (IPSET-thrombosis), and revised IPSET-thrombosis. Treatment decisions were largely made by individual physicians, taking into account patient preferences and backgrounds. Results: A total of 179 ET patients were included, and thrombotic events were observed in 26 patients. TFS was significantly longer in high-risk patients of all risk models receiving a combination of cytoreductive therapy (CRT) and antiplatelet therapy (APT) compared to CRT alone. Similar results were seen in intermediate-risk patients stratified by IPSET-thrombosis. In contrast, in very low- and low-risk patients of all risk models, TFS was not affected by addition of CRT, indicating that observation or APT alone is an appropriate treatment approach for these patients. Conclusion: We demonstrate that current guidelines provide optimal treatment approaches for Japanese ET patients under real-world clinical settings.